1989
DOI: 10.1089/dna.1.1989.8.101
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Regulation of Human α1-Antitrypsin Gene Expression in Transgenic Mice

Abstract: The 5'-flanking sequence of the human alpha 1-antitrypsin (AAT) gene contains multiple cis-regulatory elements, including a distal enhancer and proximal sequences essential for its transcription in cultured hepatoma cells. To understand better the promoter specificity of the AAT gene in vivo, transgenic mice harboring the AAT-SV40 hybrid promoter or the natural AAT promoter fused to a reporter gene (CAT) were generated. Examination of CAT activity in various tissues indicated that the CAT gene was expressed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…The nuclei were suspended in the same buffer also containing 1 mM EDTA. Nuclear proteins were extracted by the addition of 5 M KCl to a final concentration of 0.3 M. After centrifugation the final supernatant was adjusted to 0.1 M KCl by the addition of buffer A100 [20,21].…”
Section: Preparation Of Cell Extractsmentioning
confidence: 99%
“…The nuclei were suspended in the same buffer also containing 1 mM EDTA. Nuclear proteins were extracted by the addition of 5 M KCl to a final concentration of 0.3 M. After centrifugation the final supernatant was adjusted to 0.1 M KCl by the addition of buffer A100 [20,21].…”
Section: Preparation Of Cell Extractsmentioning
confidence: 99%
“…Figure 5A shows the location of restriction sites in the hAAT promoter. 24 BamH I sites are present at -46 and -1200 bp relative to the transcription initiation site; BamH I is unaffected by the methylation state of the DNA. The recognition site for both Hpa II DNA samples showed that the total signal in each lane is proportional to the amount of DNA present, making it impossible that 90% of the cells had lost expression because of deletion of the transgene.…”
Section: Analysis Of the Methylation State And The Copy Number Of Dnamentioning
confidence: 99%
“…It is minimally expressed in the adult except during injury and repair, such as following PH in mice and hepatocellular carcinoma (HCC) in mice and humans (20). In the course of studies exploring the biological role of TWEAK, we prepared a transgenic mouse expressing the gene under control of the α1 antitrypsin (AAT) promoter, which is primarily expressed in the liver (22). The livers in these mice exhibited a striking periportal outgrowth of oval cells but otherwise appeared healthy.…”
Section: Introductionmentioning
confidence: 99%